Frontispiece: Photoarylation of Iodocarboranes with Unactivated (Hetero)Arenes: Facile Synthesis of 1, 2‐[(Hetero)Aryl]n‐o‐Carboranes (n=1, 2) and o‐Carborane‐Fused Cyclics. Issue 3 (10th January 2017) - Ni, Hangcheng; Qiu, Zaozao; Xie, Zuowei
Abstract : Carboranes : In their Communication on page 712 ff., Z. Xie and co‐workers report on the transition‐metal‐free photoarylation of iodocarboranes with unactivated (hetero)arenes. A large variety of (hetero)arylated o ‐carboranes has been obtained.